Serological prevalence and haematological profile of Feline Immunodeficiency virus (FIV) in semi-roamer and outdoor cats - Mohamaddiah, N. A.; Khor, Kuan Hua; Arshad, Siti Suri; Mustaffa Kamal, Farina (Veterinary Association Malaysia, 2014)
Feline Immunodeficiency virus (FIV) is among the most common infectious diseases diagnosed in cats. In this study, 55 client-owned cats presented to the University Veterinary Hospital, Universiti Putra Malaysia (UVH-UPM) were sampled. Inclusion criteria were semi-roamer and outdoor cats aged more than 6 mont hs old. Blood samples were collected for serological testing us ing commercial immunochromatographic test kits and haematological an alysis. Of the 55 cats tested, 13 cats (23.6%) tested positive for FIV antibodies. There was a significant association (P<0.05) between neuter and health status to FIV seropositivity. FIV infect ions were more likely occured in intact cats compared to neutered cat s, and in sick cats compared to healthy cats. Erythrocytes, hemoglobin and packed cell volume (PCV) were significantly redu ced (P<0.05) in FIV cats compared to FIV-seronegative cats, however these parameters were within the normal ranges